Numerical simulation of osteocyte cell in response to directional mechanical loadings and mechanotransduction analysis: Considering lacunar–canalicular interstitial fluid flow. Issue 133 (September 2016) - Joukar, Amin; Niroomand-Oscuii, Hanieh; Ghalichi, Farzan
Highlights: Changes in osteocyte morphology and direction of loadings affect cell stimulation. Shear stress in the canaliculi which are along the loading direction is higher than other canaliculi. There was strong dependency between stimulus function, shear stress, calcium, and NO concentration. Osteocyte cells whose major axis is parallel to the loading direction experienced higher shear stresses. Abstract: The osteocyte cell is a bone cell that also functions as a bone mechanosensor. In this work, a three-dimensional (3D) fluid–structure interaction (FSI) model of an osteocyte cell under different mechanical loading conditions was used to obtain a better understanding of osteocyte cell behavior under different physiological conditions. In the current study, both fluid and solid parts of osteocyte cell were considered in order to allow for more accurate results. Five different loading conditions have been applied to the osteocyte cell, and consequently the different interstitial fluid flow velocities and shear stresses have been investigated. Furthermore, using a mathematical model, the change in the stimulus function value with shear stress and NO enzyme was revealed. This work suggests that changes in osteocyte morphology and direction of loadings affect cell stimulation. It was found that cell is mostly stimulated and expanded in the direction experiencing the most shear stress. Finally, the amount of cell stimulation was shown quantitatively and there was strong dependency between stimulus function, shear stress, calcium, and NO concentration.